Ultrasound-induced gelation of a giant macrocycle - Núñez-Villanueva, Diego (Royal Society of Chemistry, 2018)

(untitled) (Chem Commun (Camb))
A 68-membered macrocycle undergoes ultrasound-induced supramolecular gelation in acetonitrile. The sonogel shows a remarkable thermostability, indicating that self-assembly is mediated by exceptionally robust non-covalent interactions. Model compounds indicate that the macrocyclic topology is essential for gelation to occur.